Estudio de la fanpage de Facebook de la carrera de Comunicación de la Universidad Nacional de Chimborazo (Dossier: Comunicación, educación y pedagogías mediáticas) - Robalino Latorre, Mercedes Itzayana (2025)
This article analyzes the role played by the fanpage of the Communication Career of the National University of Chimborazo as an educommunicative tool in the university digital ecosystem, through a mixed approach, which combines qualitative and quantitative techniques, the contents published on this page between January 2023 and May 2024 are studied. The main objective was to identify how academic training, and the active participation of the student community are promoted through the strategic use of this social network. The research is based on a theoretical framework focused on educommunication, which allowed understanding of the communicational processes mediated by digital technologies and their potential to strengthen collaborative learning. the results show that the fanpage not only fulfills an informative function, but also contributes to the dissemination of academic events, to the reflection on contemporary social problems and to the dynamization of university life. One of the most relevant findings is the role of digital interaction as a key factor in the construction of an active and participatory community, it is concluded that a conscious and coherent educommunicative management of content allows transforming the fanpage into a space for linking, innovation and institutional strengthening, reaffirming the role of Facebook as an educational platform in higher education.